Life is sweet: the cell biology of glycoconjugates - Broussard, Alex C. (Mol Biol Cell, 2019)
Cells are dazzling in their diversity, both within and across organisms. And yet, throughout this variety runs at least one common thread: sugars. All cells on Earth, in all domains of life, are literally covered in glycans, a term referring to the carbohydrate portion of glycoproteins and glycolipids. In spite of (or, perhaps, because of) their tremendous structural and functional complexity, glycans have historically been underexplored compared with other areas of cell biology. Recently, however, advances in experimental systems and analytical methods have ushered in a renaissance in glycobiology, the study of the biosynthesis, structures, interactions, functions, and evolution of glycans. Today, glycobiology is poised to make major new contributions to cell biology and become more fully integrated into our understanding of cell and organismal physiology.